Loss of control eating during pregnancy is associated with excessive gestational weight gain among individuals with overweight and obesity - Michele D. Levine; Rebecca L. Emery Tavernier; Rachel P. K. Conlon; Jennifer L. Grace; Gina M. Sweeny; Bang Wang; Yu Cheng (BMC, 2023)
Abstract Background Excessive gestational weight gain (GWG) predicts negative health outcomes among individuals with overweight or obesity. Loss of control eating (LOC), the ingestion of food associated with being unable to control eating, is the core psychopathology of binge eating disorders. We evaluated the contribution of LOC to GWG among pregnant individuals with prepregnancy overweight/obesity. Methods In a prospective longitudinal study, individuals with prepregnancy BMI ≥ 25 (N = 257) were interviewed monthly to assess LOC and reported demographic, parity, and smoking information. GWG was abstracted from medical records. Results Among individuals with prepregnancy overweight/obesity, 39% endorsed LOC prior to or during pregnancy. After adjusting for factors that have previously been linked to GWG, LOC during pregnancy, uniquely predicted higher GWG and greater likelihood of exceeding GWG recommendations. Participants with prenatal LOC gained 3.14 kg (p = 0.03) more than did those without LOC during pregnancy and 78.7% (n = 48/61) exceeded IOM guidelines for GWG. The frequency of LOC episodes was also associated with greater weight gain. Conclusions Prenatal LOC is common among pregnant individuals with overweight/obesity and predicts greater GWG and increased likelihood of exceeding IOM GWG guidelines. LOC may represent a modifiable behavioral mechanism to prevent excessive GWG among individuals at risk for adverse pregnancy outcomes.